Liver Transplantation Using Hepatitis C Virus–Viremic Donors Into Hepatitis C Virus–Aviremic Recipients as Standard of Care. Issue 4 (20th April 2021) - Bohorquez, Humberto; Bugeaud, Emily; Bzowej, Natalie; Scheuermann, Jennifer; Hand, Jonathan; Bruce, David; Carmody, Ian; Cohen, Ari; Joshi, Shobha; Seal, John; Sonnier, Dennis; Therapondos, George; et al.
Abstract : Liver transplantation (LT) using allografts from hepatitis C virus (HCV)‐viremic/nucleic acid testing–positive donors' (DNAT+) organs into HCV‐aviremic recipients (rHCV−) has been limited owing to nearly universal HCV transmission and concerns regarding availability, safety, and efficacy post‐LT with direct‐acting antiviral (DAA) therapy. We report our experience of LT using DNAT+ organs into rHCV− as a routine standard of care. Following verification of DAA access, absence of critical drug‐drug interactions (DDIs) with DAAs, and informed consent, allocated DNAT+ organs were offered to patients on the waiting list for LT irrespective of recipient HCV status. Between June 2018 and December 2019, 292/339 rHCV− received an LT. Forty‐seven patients were excluded from analysis because of recipient HCV viremia, refusal to receive DNAT+ organs, or inability to receive DAA therapy post‐LT. Of these 292 patients, 61 rHCV− received DNAT+ livers (study group), and 231 rHCV− received DNAT− (aviremic donors [nuclear acid test‐negative donors]) livers (control group). Recipient and donor characteristics as well as 1‐year post‐LT patient and graft survival were similar between groups. In the study group, 4 patients died, and 1 patient required retransplantation within the first year post‐LT (all unrelated to HCV); 56 patients received DAA therapy, with a median time from LT to the start of DAA treatment of 66.9 days (interquartile range [IQR], 36‐68.5), and 51 patients completed DAA treatment, all achieving sustained virologic response for 12 or more weeks (SVR‐12) (1 patient required retreatment owing to relapse following initial DAA therapy). No patients had evidence of fibrosing cholestatic hepatitis or extrahepatic manifestations of HCV. This report indicates that transplantation of DNAT+ livers into rHCV− and subsequent DAA therapy is associated with clinical outcomes comparable to those achieved with DNAT− allografts.